Development of an Interactive 360° Video of the Kesawan Old Town Area in Medan Using the MDLC Model - Heri Kurniawan; Abdul Khaliq; Nova Mayasari; Feri Rinto Bashari (Journal of Information Technology, computer science and Electrical Engineering, 2025)
The development of multimedia technology offers significant opportunities in digital tourism promotion. The Kesawan Old Town area in Medan has high historical and architectural value but has not been optimally utilized through modern interactive media. This study aims to develop an interactive 360° video as a digital promotional medium for the Kesawan heritage district. The development method used is the Multimedia Development Life Cycle (MDLC), consisting of six stages: concept, design, material collecting, assembly, testing, and distribution. Data were obtained by direct video capture using an Insta360 camera along Ahmad Yani Street, covering Tjong A Fie Mansion, London Sumatra Building, Tip Top Restaurant, and several Dutch colonial heritage buildings. The result is interactive 360° video showcasing immersive visual panoramas of the Kesawan area. Technical testing showed that all interactive features operated properly and were compatible across desktop and mobile devices. The media is considered effective in enhancing visual appeal and supporting digital tourism promotion for the Kesawan heritage area.